Effect of Dietary β-hydroxy-β-methylbutyrate Calcium on Carcass Cuts, Serum Biochemistry, Bone Characteristics and Digestive Tract pH of Broiler Chickens - Ahmed , Suad Kh.; Rasheed, Eman Allaa (International Journal of Poultry Science, 2017)
Objective: This study aimed to investigate the effect of dietary β-hydroxy-β-methylbutyrate calcium (HMB-Ca) on the main carcass cuts, serum biochemistry, bone characteristics and digestive tract pH of broiler chickens. Materials and Methods: A total of 216 day-old chicks of strain Ross-308 were distributed into 4 groups dietary fed HMB-Ca at different concentrations (0.0, 0.1, 0.15 and 0.2%). The HMB-Ca was administered from 1-35 days of age. Duncan’s multiple range test was used to compare means. Results: The results showed that 0.2% HMB-Ca increased (p